The Science of Well-Being 2005
DOI: 10.1093/acprof:oso/9780198567523.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

* The developmental origins of well-being

Abstract: Low birthweight is now known to be associated with increased rates of coronary heart disease and the related disorders, stroke, hypertension and adult-onset diabetes. These associations have been extensively replicated in studies in different countries and are not the result of confounding variables. They extend across the normal range of birthweight and depend on lower birthweights in relation to the duration of gestation rather than the effects of premature birth. The associations are thought to be consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 23 publications
2
92
0
3
Order By: Relevance
“…Research has suggested that an insult to nutrition of the dam during gestation can influence the long-term health and productivity of offspring through a process that has been termed fetal, or developmental, programming (Barker, 2004;Wu et al, 2006;Reynolds et al, 2010). A growing body of evidence suggests that gestational nutrition can alter offspring body composition and growth, hormonal balance, cardiovascular development, metabolic function, neonatal health, organ development and function (Wu et al, 2006;Long et al, 2009), and gene expression (Long et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that an insult to nutrition of the dam during gestation can influence the long-term health and productivity of offspring through a process that has been termed fetal, or developmental, programming (Barker, 2004;Wu et al, 2006;Reynolds et al, 2010). A growing body of evidence suggests that gestational nutrition can alter offspring body composition and growth, hormonal balance, cardiovascular development, metabolic function, neonatal health, organ development and function (Wu et al, 2006;Long et al, 2009), and gene expression (Long et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have suggested that infant weight (which reflects the rate of weight gain) is more important than birth weight in predicting adult chronic diseases (Eriksson et al 2003). Additionally, a number of studies have shown that rapid weight gain (i.e., catch-up weight gain) is associated with later obesity and chronic adult diseases, such as cardiovascular disease and type 2 diabetes (Eriksson et al 2003;Barker 2004;Eriksson 2005).…”
mentioning
confidence: 99%
“…Use of the porcine centile reference curves Increasing birth weight and ensuring optimal growth in the first year of life can reduce the risk of coronary heart disease (Barker, 2004). Similarly, thinness at birth and at 1 year of age are associated with early adiposity rebound (when BMI decreases in early childhood before increasing again between 3 and 8 or more years of age), which is associated with impaired glucose tolerance (Bhargava et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Poor weight gain and slow growth have been linked to cot death (Sinclair-Smith et al, 1976), developmental delay (Dowdney et al, 1987), ischaemic heart disease (Barker et al, 1989), non-insulindependent diabetes and hypercholesterolaemia (Barker, 1995a and1995b). The Developmental Origins of Adult Disease (DOAD) hypothesis proposes that pre-and postnatal growth and development influence health in later life (Barker, 2004).…”
Section: Introductionmentioning
confidence: 99%